Impact of Anti-Retroviral Treatment and Cotrimoxazole Prophylaxis on Helminth Infections in HIV-Infected Patients in Lambaréné, Gabon. - Saskia Janssen; Sabine Hermans; Martijn Knap; Alma Moekotte; Elie G Rossatanga; Akim A Adegnika; Sabine Bélard; Thomas Hänscheid; Martin P Grobusch (Public Library of Science (PLoS), 2015)
Background Foci of the HIV epidemic and helminthic infections largely overlap geographically. Treatment options for helminth infections are limited, and there is a paucity of drug-development research in this area. Limited evidence suggests that antiretroviral therapy (ART) reduces prevalence of helminth infections in HIV-infected individuals. We investigated whether ART exposure and cotrimoxazole preventive therapy (CTX-P) is associated with a reduced prevalence of helminth infections. Methodology and principal findings This cross-sectional study was conducted at a primary HIV-clinic in Lambaréné, Gabon. HIV-infected adults who were ART-naïve or exposed to ART for at least 3 months submitted one blood sample and stool and urine samples on 3 consecutive days. Outcome was helminth infection with intestinal helminths, Schistosoma haematobium, Loa loa or Mansonella perstans. Multivariable logistic regression was used to assess associations between ART or CTX-P and helminth infection. In total, 408 patients were enrolled. Helminth infection was common (77/252 [30.5%]). Filarial infections were most prevalent (55/310 [17.7%]), followed by infection with intestinal helminths (35/296 [11.8%]) and S. haematobium (19/323 [5.9%]). Patients on CTX-P had a reduced risk of Loa loa microfilaremia (adjusted odds ratio (aOR) 0.47, 95% CI 0.23-0.97, P = 0.04), also in the subgroup of patients on ART (aOR 0.36, 95% CI 0.13-0.96, P = 0.04). There was no effect of ART exposure on helminth infection prevalence. Conclusions/significance CTX-P use was associated with a decreased risk of Loa loa infection, suggesting an anthelminthic effect of antifolate drugs. No relation between ART use and helminth infections was established.